Negotiating Resilience with Hard and Soft City - Singh, Binti; Berger, Tania; Parmar, Manoj (Urban Futures, 2023)
This book explores how cities are shaped by the lived experiences of inhabitants and examines the ways they develop strategies to cope with daily and unexpected challenges. It argues that migration, livelihood, and public health challenges result from inadequacies in the hard city-urban assets, such as land, infrastructure, and housing, and asserts that these challenges and escalating vulnerabilities are best negotiated using the soft city-social capital and community networks. In so doing, the authors criticise a singular knowledge system and argue for a granular, nuanced understanding of cities-of the interrelations between people in places, everyday urbanisms, social relationships, cultural practices, and histories. The volume presents perspectives from the Global South and the Global North and engages with city-specific cases from Africa, India, and Europe for a deeper understanding of resilience. Part of the Urban Futures series, it will be of great interest to students and researchers of urban studies, urban planning, urban management, architecture, urban sociology, urban design, ecology, conservation, and urban sustainability. It will also be useful for urbanists, architects, urban sociologists, city and town planners, policy makers, and those interested in a deeper understanding of the contemporary and future city.